2003
DOI: 10.1243/095441103770802531
|View full text |Cite
|
Sign up to set email alerts
|

Yielding of the clamped-wire system in the Ilizarov external fixator

Abstract: This study demonstrates that the clamped-wire system used to suspend bones within an Ilizarov external fixator yields when the perpendicular load exceeds 50 N per wire. Cyclic loading was applied to tensioned wires clamped within an Ilizarov ring component, with steadily increasing load amplitude. Wires were tested at four initial tension settings. The amount of energy lost within the clamped-wire system per load cycle was calculated for every test. The results showed that there was a consistent trend to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
1
25
0
3
Order By: Relevance
“…Some authors believe that slippage is responsible for the loss of pre-tension (Aronson andHarp 1992, Renard et al 2005), while others have shown that material yield (Hillard et al 1998) or a combination of material yield and wire slippage (Delprete and Gola 1993, Watson et al 2003b, Osei et al 2006 cause the loss of pre-tension in the wires.…”
mentioning
confidence: 99%
“…Some authors believe that slippage is responsible for the loss of pre-tension (Aronson andHarp 1992, Renard et al 2005), while others have shown that material yield (Hillard et al 1998) or a combination of material yield and wire slippage (Delprete and Gola 1993, Watson et al 2003b, Osei et al 2006 cause the loss of pre-tension in the wires.…”
mentioning
confidence: 99%
“…Thus, the FEA in the present study can be used to verify the analytical solutions as given in §3. Watson et al (2000Watson et al ( , 2003b have published the results from their experimental work for displacements of a K-wire (DZ180 mm and dZ1.8 mm) loaded perpendicular to its longitudinal axis at its midpoint, under different pretensions, in two graphs ( fig. 5 of Watson et al 2000Watson et al , 2003b.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al (2000Watson et al ( , 2003b have published the results from their experimental work for displacements of a K-wire (DZ180 mm and dZ1.8 mm) loaded perpendicular to its longitudinal axis at its midpoint, under different pretensions, in two graphs ( fig. 5 of Watson et al 2000Watson et al , 2003b. The results in figure 8 of this paper, which are based on the analytical solutions, are comparable with the results shown in either of those graphs.…”
Section: Discussionmentioning
confidence: 99%
“…The compression load was increased from 0 to 100 N at a rate of 10.0 N/s for each test. Loads were kept at relatively low levels to avoid yielding of the tensioned thin wire fixation based on the results of a study that showed the maximum sustainable transverse wire load before clamp yielding was 50 N per wire (Watson et al, 2003) and to simulate the early controlled loading associated with rehabilitation. The proximal load plate offset the medial and posterior loading by 4 cm and posteromedial loading was offset by 5.7 cm.…”
Section: Methodsmentioning
confidence: 99%